Ocean exergy and energy conversion systems - Miguel, A. F. (2012)
Oceans store energy in the form of currents, waves, tides, heat and salinity that can help to alleviate worldwide demand for power and the global climate change threat. They also store a considerable amount of an isotope of hydrogen (deuterium) which takes part in the most promising fusion reactions. Exergy analysis can be applied to evaluate the work potential (extractable) of a resource. This paper focuses on the exergy content of ocean reservoirs and provides a review of the technology installed for harvesting ocean energy.